Bmpr2 mutant mice are an inadequate model for studying iron deficiency in pulmonary hypertension. (20th December 2022) - Zhang, Vida; Ganz, Tomas; Nemeth, Elizabeta; Umar, Soban; Kim, Airie
Abstract: As bone morphogenetic protein receptor type II (Bmpr2) mutations are the most common genetic cause of pulmonary arterial hypertension (PAH), and iron deficiency (ID) is associated with worse clinical outcomes in PAH patients, we proposed to use Bmpr2 ± mice to induce a model of ID in pulmonary vascular disease. Our study shows that these transgenic mice are not a good model for this clinical phenomenon.